2020
DOI: 10.2147/dddt.s272355
|View full text |Cite
|
Sign up to set email alerts
|

<p>Astragaloside IV: An Effective Drug for the Treatment of Cardiovascular Diseases</p>

Abstract: Cardiovascular disease (CVD), the number one cause of death worldwide, has always been the focus of clinical and scientific research. Due to the high number of deaths each year, it is essential to find alternative therapies that are safe and effective with minimal side effects. Traditional Chinese medicine (TCM) has a long history of significant impact on the treatment of CVDs. The mode of action of natural active ingredients of drugs and the development of new drugs are currently hot topics in research on TCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 102 publications
1
35
0
Order By: Relevance
“…For example, the flavonoids in Astragali Radix can regulate immunity, inhibit inflammation and oxidative stress, and have antitumor activity [ 20 23 ]. Saponins can improve CI by regulating biological processes such as energy metabolism disorder, depolarization around the infarct, oxidative stress damage, inflammatory response, and apoptosis in CI [ 24 26 ]. Alkaloid components and pyrazine components play a role in scavenging free radicals and antioxidation by downregulating immune cells and inflammatory factors, so as to reduce brain damage [ 27 – 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the flavonoids in Astragali Radix can regulate immunity, inhibit inflammation and oxidative stress, and have antitumor activity [ 20 23 ]. Saponins can improve CI by regulating biological processes such as energy metabolism disorder, depolarization around the infarct, oxidative stress damage, inflammatory response, and apoptosis in CI [ 24 26 ]. Alkaloid components and pyrazine components play a role in scavenging free radicals and antioxidation by downregulating immune cells and inflammatory factors, so as to reduce brain damage [ 27 – 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Doses of ASI ranging from 25 to 50 mg/kg have produced markedly therapeutic pharmacological effects ( Wang et al, 2017 ; Yang L. et al, 2020 ). ASI is administered intraperitoneally ( Wang et al, 2017 ), and anti-inflammatory properties that benefit diabetes treatment have been observed ( Xie and Du, 2011 ; Tan et al, 2020 ; Zhou X. et al, 2020 ). In addition, in the EAE model, ASI inhibits the differentiation and maturation of dendritic cells by inhibiting CD11c, CD86, CD40, and MHC II activation.…”
Section: Nature Productsmentioning
confidence: 99%
“…Astragaloside IV (AS-IV, C 41 H 68 O 14 , Figure 1 ), a cycloartane-type triterpene glycoside chemical, is a major compound in the aqueous extract from Astragalus membranaceus ( Zhang et al, 2020 ). Many studies have demonstrated that AS-IV can protect the cardiovascular system, lungs, kidneys and brain, an effect attributed to its anti-inflammatory, antioxidant, anti-apoptotic and immunoregulation properties ( Yan et al, 2017 ; Meiqian et al, 2018 ; Zhang et al, 2019 ; Tan et al, 2020 ). It has been shown that AS-IV could counter inflammation through multiple signaling pathways, such as Toll like receptor four/nuclear factor–kappa B (TLR4/NF-κB) signaling pathway, mitogen-activated protein kinases (MAPK) signaling pathway, and Janus kinase two/signal transducer and activator of transcription 6 (JAK2/STAT6) signaling pathway ( Leng et al, 2019 ; Yang and Wang, 2019 ; Hsieh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%